KOTA BANDUNG SEBAGAI SUBNATIONAL GOVERNMENT DALAM KERJASAMA SMART CITY DENGAN KOTA SEOUL TAHUN 2016-2019 - Bramastya, Randy; Septiarika, Fahrisya Tiko (Universitas Panca Marga, 2020)
International relations has experienced an expansion of actors. Liberalism serves as gate to welcome the widest possible space for international actors to be involved in foreign affairs in a transnational relationship according to Keohane and Nye. These international actors are also not restricted to the private sector, but also local governments. This paper examines the stronger role of local governments according to Duchacek and Soldatos as subnational government actors which establish relationships with other subnational governments or local governments appointed as partners. This study, the government of Bandung City and the partner city, Seoul, established international activities through the Smart City collaboration, whose implementation can be recognized in the 2016-2019 Sister City partnership. This study aims to determine in role of the Bandung city municipal as a subnational government based on policy advocay and its transnational relations built through a qualitative approach that it can present a descriptive explanation. This study uses a literature study approach that links secondary data as an explanation. Secondary data used include reports from KSP, smart city development master plans, and other sources. This study comes to the conclusion that the Bandung City government through Law Number 23 of 2014 is given the authority to be able to carry out foreign cooperation which is a representation to carry out complementary functions to take care of foreign affairs which can benefit its jurists